PASCAL PROGRAMMING MODULE DEVELOPMENT IN MATHEMATICS EDUCATION COURSES - Chandra, Rodi (RC-INSTITUT, 2018)
This thesis has an aim to develop The Pascal Programmed validity, practicality, and affectivity for students at Mathematic Department of STKIP PGRI WEST SUMATERA. The method that is used in this research is developmental research approach. There are three steps, such as: front – end analysis, prototype, and assessment steps.           In the front – end research, the activity is done through analyzed the material that is coursed, the Pascal programmed text books, interviewed the colleagues; they are lecturers who teach the related subjects, and learn student’s characteristics. Based on the result of front – end analysis, I have been gotten the Pascal programmed of prototype front – end module, and then it is consulted with the scientists. Then the prototype is validated by seven scientists, they are; three construction scientists from State University of Padang and STMIK Indonesia, and four content scientists from State University of Padang and STKIP PGRI West Sumatera.            The practicality in this activity was tried to the mathematic educated department students of STKIP PGRI West Sumatra at second semester, and monitored by two monitoring lecturers. It is done as same as practicality step. It is monitored through; the college student’s activity, motivation, and result of the study. The result of the study is showed; 1) the Pascal programmed module was used which had valid (content and construct validity) from media, technology, and mathematic of education scientists point of view; 2) there were no the important problems in using of this program based on observer, lecturers, and student’s assessment; and 3) The using of this module had affectivity that is showed from the activity, motivation, and result of the student’s study that it can be shown from the students who got high scores after they followed this study.